Proposal and validation of a questionnaire of evaluation of the online teaching practice through the student opinion - LOPEZ-DIAZ, Jose Alberto (2018)
Teaching evaluation is a process in which improvements can be done in the teaching-learning process. The students are the ones who can evaluate teaching activity according to their experience and satisfaction in relation to the acquired knowledge. The objective of this project was to create an assessment instrument of the online teaching practice through student feedback. This study collected comments of 110 students that have taken online courses at the Autonomous University of Ciudad Juarez (UACJ). A questionnaire of 16 items with Likert scale was drawn up, considering the course organization, pedagogical dynamics, evaluation, and personal and academic traits. The opinion of the students was transcribed, classified, and codified in similar conceptual variables; from this analysis the questionnaire was restructured resulting in an instrument of 13 items. This instrument was evaluated on an online pilot test applied to 441 students from online courses. The validation of this instrument was estimated through reliability testing based on Cronbach’s alpha. The analysis of the internal consistency of the instrument based on the Cronbach’s alpha was 0.9. The evaluation of this coefficient is rated as excellent, so the instrument is viable and reliable to evaluate the teaching practice of online courses at UACJ.